Frontoparietal Attentional Network Activation Differs Between Smokers and Nonsmokers during Affective Cognition - Froeliger, Brett (2012)
Smoking withdrawal-induced disruption of affect and cognition is associated with dysregulated prefrontal brain function although little is known regarding the neural foci of smoker-nonsmoker differences during affective cognition. Thus, the current study utilized fMRI to identify smoker-nonsmoker differences in affective cognition. Thirty-four healthy volunteers (17 smokers, 17 nonsmokers) underwent fMRI during an affective Stroop task (aST). The aST includes emotional cue-reactivity trials, and response selection trials that contain either neutral or negative emotional distractors. Smokers had less activation during negative cue-reactivity trials in regions subserving emotional awareness (i.e. posterior cingulate), inhibitory control (i.e. inferior frontal gyrus) and conflict resolution (i.e. anterior cingulate); whereas during response selection trials with negative emotional distractors, smokers had greater activation in a frontoparietal attentional network (i.e. middle frontal and supramarginal gyri). Exploratory analyses revealed that task accuracy was positively correlated with ACC and IFG BOLD response. These findings suggests that chronic nicotine use may reduce inhibitory control and conflict resolution of emotional distraction, and result in recruiting additional attentional resources during emotional interference on cognition.